Your Florida Dooryard Citrus Guide - Young Tree Care - James J. Ferguson (EDIS)
This document is HS 887, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Originally published in hardcopy, 1995. Publication date: August, 2002.